I understand the proof of the identity in the title for $A$ Hermitian. One uses that any Hermitian matrix can be diagonalized as $A = X \Lambda X^{-1}$, such that $$ \det{A} = \prod_i \lambda_i, $$ and we have $$ \exp(Tr(\log(A)) = \exp(Tr(X\log\Lambda X^ {-1}) = \exp(\sum_i\log(\lambda_i)) = \prod_i \lambda_i. $$

However, is it possible to show the identity for $A$ not Hermitian? My motivation for this question is that in physics the identity is often used without it being clear that $A$ is Hermitian.

  • $\begingroup$ You do need to assume $A$ is nonsingular, else $\ln(A)$ doesn't make sense. $\endgroup$ – Robert Israel Oct 19 '15 at 17:24

If $\ln(A) = B$, the identity says

$$ \det(\exp(B)) = \exp(\text{Tr}(B)) $$

which is more usual form for this identity, true for all $n \times n$ matrices $B$ over $\mathbb C$ (avoiding questions about whether $\ln(A)$ is defined, and which of the possible logarithms to use).

One way to do this is to show it first for diagonalizable matrices $B$, then use the fact that diagonalizable matrices are dense and both sides of the equation are continuous functions of $B$.

A second way is to use Jordan canonical form.

A third way is to note that both $\det(\exp(tB))$ and $\exp(t \text{Tr}(B))$ satisfy the differential equation $y' = \text{Tr}(B) y$ with initial value $y(0) = 1$.

| cite | improve this answer | |
  • 1
    $\begingroup$ Wikipedia's page on Jacobi's identity treats this identity as a corollary of Jacobi's identity using the third proof method, with the Jacobi identity being used to obtain $\frac{d}{dt}\det(\exp(t B))$. $\endgroup$ – Semiclassical Sep 2 '19 at 16:48

Here is an elegant proof with minimal assumptions (only non-singular and square):

\begin{align} \rm{Det}(e^{B}) &= \displaystyle \lim_{N \to \infty} \rm{Det}\Big(e^{B/N}\Big)^{N} \\ &= \displaystyle \lim_{N \to \infty} \rm{Det} \Big(1 + \frac{B}{N}\Big)^{N} \\ &= \displaystyle \lim_{N \to \infty} \Big(1 + \frac{\rm{Tr}B}{N}\Big)^{N} \\ &= e^{\rm{Tr}B} \end{align}

Now take log on both sides and put $ e^{B} = A$ to get the result.

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.